Digital Transformation and Big Data - Stanislav S. Kuzora; Ivan P. Natarov (RUDN Journal of Public Administration, 2022)
Today, the Russian Federation pays special attention to the digital transformation of the country as a whole and shows a separate interest in big data in particular, which is confirmed by a number of analyzed documents and the current situation in the subject area. The research work proposed for reading is devoted to the analysis of big data, one of the areas of use of which is the state, or rather the work of federal and regional executive authorities. The main value of big data from the position of the state is seen in the possibility of working on volumes of heterogeneous information in order to increase efficiency in making managerial decisions on a wide range of issues. The main purpose of the study is to disseminate the experience of big data analysis, which is used in the work of the Ministry of Economic Development of Primorsky Krai. To do this, it is proposed to turn to the theoretical aspects of big data, find out the main chain of work on them, and also pay attention to domestic and foreign experience in using data in some areas of knowledge. The practical part of the study is a description of the experience of the Ministry of Economic Development of the PC, which is directly related to the digital development of the region and carries out a certain list of works with heterogeneous data. As an example, attention is drawn to a proven approach to the analysis of a large set of open data characterizing the work and development of small and medium-sized businesses in the Primorsky Territory, posted on the website of the Federal Tax Service of the Russian Federation. In conclusion, it is emphasized that the approach proposed in the study for working with data can be adapted to similar needs in other federal and regional authorities